Brand Love and Customer Engagement in Social Commerce Platforms among Indonesian Consumers - Frans Sudirjo; Olayinka Funmi Babatunde; Precious Ayoade Arowolo; Ademola Mutiu Adekunle (Eastasouth Institute, 2026)
This study investigates the relationships between brand affinity, customer engagement, and customer loyalty within social commerce platforms among Indonesian consumers. Grounded in relationship marketing and the Stimulus–Organism–Response (S-O-R) framework, the research adopts a quantitative approach to examine both direct and indirect effects among the constructs. Data were collected from 150 respondents using a structured questionnaire measured on a five-point Likert scale. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The results reveal that brand affinity has a significant positive effect on customer engagement and customer loyalty. Customer engagement also significantly influences customer loyalty, indicating its dominant role in shaping consumer commitment. Furthermore, mediation analysis confirms that customer engagement partially mediates the relationship between brand affinity and customer loyalty. These findings suggest that emotional attachment to a brand must be translated into active interaction to effectively generate loyalty in social commerce environments. This study contributes to the literature by integrating emotional and behavioral constructs within a unified framework and provides empirical evidence from an emerging market context. Practically, the findings offer strategic insights for businesses to enhance customer relationships through engagement-driven marketing approaches, thereby strengthening long-term loyalty in increasingly competitive digital marketplaces.